Impact of transition to a low carbon power system on the GB gas network. (1st August 2015) - Qadrdan, Meysam; Chaudry, Modassar; Jenkins, Nick; Baruah, Pranab; Eyre, Nick
Highlights: Availability and cost of gas are crucial factors in power system planning. CGEN+ was developed to analyse expansion of combined gas and electricity systems. Performance of various low carbon strategies were assessed. Electrification of heat and transport requires large investment in power sector. Despite declining demand for gas, peak gas demand will almost remain unchanged. Abstract: The reliance of Great Britain power generation on the gas network makes it critical to consider the future availability and cost of gas in planning the expansion of the power system. A combined gas and electricity network planning model was used to investigate impacts of various low carbon strategies on regional expansion of the Great Britain gas network out to the 2050s. A number of long term energy supply and demand strategies covering a range of plausible investment policies for Great Britain gas and electricity systems were explored. Reliance of Great Britain on gas imports was projected to vary from 84%, in an energy system with significant electrification of heat and transport sectors and large capacity of nuclear generation, to 94% in a business as usual case. Extensive investment in Liquefied Natural Gas import facilities at Milford Haven and the Isle of Grain was shown to compensate for reduction of indigenous gas supplies. Exploitation of shale gas in north England was shown to reduce the gas dependency of Great Britain in the business as usual case to 74%. Electrification of the heat and transport sectors combined with exploitation of shale gas in Great Britain could reduce import dependency to below 10% by 2050.